Interreligious Dialogue in Indonesia: Reading Fakfak’s Interfaith Experiences Through Paul F. Knitter - Marthinus Ngabalin; Izak Y.M Lattu; Listyani Listyani (Jurnal Sosiologi Reflektif, 2026)
Interreligious dialogue has become an urgent necessity in plural societies because social peace cannot be sustained through formal tolerance alone, but must also be grounded in shared everyday practices rooted in local culture. This study aims to analyse the relevance and implementation of Paul F. Knitter’s thought in the socio-religious life of the people of Fakfak. This research employs a qualitative method with an ethnographic approach to understand the meanings, social practices, and value systems that support interreligious dialogue in Fakfak Regency, Indonesia. Data were collected through participant observation, in-depth interviews, and documentation involving religious leaders and customary leaders selected purposively. Data analysis was conducted through the stages of attending to experience, transcribing experience, analysing experience, and reading experience, and was further strengthened by the interactive model of Miles and Huberman, which includes data reduction, data display, and verification. The findings show that interreligious dialogue in Fakfak is concretely manifested through the practices of Gereja Maghi and Mesjid Maghi, interfaith mutual cooperation in the construction of houses of worship, reciprocal participation in religious celebrations, and kinship relations across different faiths. The study also reveals that the philosophy of Satu Tungku Tiga Batu, together with the values of Idu-idu, Mani-Nina, and Jojor, serves as a socio-cultural foundation that reinforces interreligious harmony. The implication of this study is that the strengthening of interreligious harmony in Indonesia needs to be built through the integration of interfaith dialogue and local wisdom as a contextual and sustainable social praxis.   Dialog antaragama menjadi kebutuhan penting dalam masyarakat majemuk karena perdamaian sosial tidak cukup dibangun melalui toleransi formal, tetapi juga melalui praktik hidup bersama yang berakar pada budaya lokal. Penelitian ini bertujuan untuk menganalisis relevansi dan implementasi pemikiran Paul F. Knitter dalam kehidupan sosial-keagamaan masyarakat Fakfak, Indonesia. Penelitian ini menggunakan metode kualitatif dengan pendekatan etnografi untuk memahami makna, praktik sosial, dan sistem nilai yang menopang dialog antaragama di Kabupaten Fakfak. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi terhadap tokoh agama serta tokoh adat yang dipilih secara purposif. Analisis data dilakukan melalui tahapan attending to experience, transcribing experience, analyzing experience, dan reading experience, lalu diperdalam dengan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan verifikasi. Hasil penelitian menunjukkan bahwa dialog antaragama di Fakfak terwujud secara nyata melalui praktik Gereja Maghi dan Mesjid Maghi, gotong royong lintas agama dalam pembangunan rumah ibadah, partisipasi timbal balik dalam perayaan keagamaan, serta relasi kekeluargaan lintas iman. Temuan ini juga menegaskan bahwa falsafah Satu Tungku Tiga Batu, bersama nilai Idu-idu, Mani-Nina, dan Jojor, menjadi fondasi sosial-kultural yang memperkuat harmoni antarumat beragama. Implikasi dari penelitian ini adalah bahwa penguatan kerukunan antarumat beragama di Indonesia perlu dibangun melalui integrasi dialog lintas iman dan kearifan lokal sebagai praksis sosial yang kontekstual dan berkelanjutan.